Dari Medan Perang Meksiko ke Strategi Perang Saudara: Transformasi Pengalaman Tempur Jenderal Ulysses S. Grant - Harefa, Faonaso (Universitas Negeri Malang, 2025)
This study was motivated by the urgency to understand how combat experience forms an effective and adaptive military strategy in the context of Sishankamrata. By using a mixed methods approach, quantitative correlation, and qualitative analysis through historical case studies. This study examined the influence of war experience on the war strategy, focusing on the figure of General Ulysses S. Grant. The results showed a very strong correlation (r = 0.979) between combat experience and military strategy development. This indicates that experience on the battlefield contributes greatly to forming effective intuition, decision-making, and strategic leadership. Novelty This study lies in the integration of experiential learning theory and adaptive leadership in analyzing causal relationships between combat experience and military strategy, which has not been widely studied in depth in academic literature. This study contributes to enriching the Sishankamrata framework by emphasizing the importance of empirical learning in forming adaptive strategic leadership while offering a historical-comparative perspective for the development of a responsive global military strategy of the dynamics of modern conflict. The limitation of this study lies in the focus on one single figure, namely General Ulysses S. Grant, so that generalizations to the context of military and civilian leaders in history are still limited; however, this finding still has theoretical and practical significance because it opens new insights on how combat experience can be converted into an effective military strategy and adaptive civilian leadership. Keywords: History of War, Sishankamrata, Mixed Methods.